The use of homemade food selling and delivery applications: investigating the adoption and post-adoption among Saudi female micro-entrepreneurs - Alsultan, Wala Sultan (2023)
On a global scale, businesses have effectively utilised intermediary digital marketplaces, such as Amazon and Alibaba by implementing a range of optimal strategies that integrate these platforms into their business models. Various intermediary mobile applications exist to provide support for micro-entrepreneurs engaged in the production of handmade food across diverse contexts, like Curryful and The Chef. The existing body of literature pertaining to female micro-entrepreneurs in Saudi Arabia who operate home-based businesses examines the advantages and drawbacks associated with commonly used trading platforms in the country, such as social media and intermediary physical shops. However, this literature fails to address the adoption and post-adoption phenomena of homemade food selling and delivery applications that have emerged in the Saudi homemade food sector in recent times. Furthermore, there is a dearth of scholarly research in the domain of Information Systems that investigates the adoption and usage of this technology, specifically within the context of handmade food businesses in other contexts. In contrast, a considerable body of research exists that examines the adoption and implementation of comparable technologies in diverse business sectors across multiple industries. In addition, most Saudi micro-entrepreneurs have not yet discovered the potential of using these marketplaces to support their homemade food businesses.